(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
the article mainly contains information about the importance of the development of pilgrimage tourism in the development of tourism. We know that in the countries rich in history, we can observe many activities related to religious or pilgrimage tourism. In addition, information was given about the directions of development of all infrastructure related to the development of pilgrimage. The article also analyzes the opinions of scientists who worked on pilgrimage tourism and gave conclusions and suggestions.